A Chaos-Based Substitution Box (S-Box) Design with Improved Differential Approximation Probability (DP) - Khan, M.A. (Springer International Publishing, 2018)
Substitution box is a vital and the only nonlinear component of modern encryption algorithm. S-box is introduced as a confusion component to resist against differential cryptanalysis. Chaos-based encryption is well liked because it exhibits similarity like cryptography. However, chaotic S-boxes possess high maximum differential approximation probability, measured using difference distribution table (DDT) for differential cryptanalysis. Therefore, this paper reports a systematic design methodology to generate chaotic S-box utilizing DDT and that can be used in multimedia encryption algorithms. DDT within the design loop is used to optimize differential approximation probability. The proposed S-box shows very low differential approximation probability as compared to other chaos-based S-box designed recently, while maintaining good cryptographic properties and high value of linear approximation probability. The strength of the proposed cryptographically strong S-box is vetted in the practical implementation of multimedia encryption. Â© 2018, Shiraz University.